2018
DOI: 10.3389/fpls.2018.00797
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CsCaM3 Improves High Temperature Tolerance in Cucumber

Abstract: High temperature (HT) stress affects the growth and production of cucumbers, but genetic resources with high heat tolerance are very scarce in this crop. Calmodulin (CaM) has been confirmed to be related to the regulation of HT stress resistance in plants. CsCaM3, a CaM gene, was isolated from cucumber inbred line “02-8.” Its expression was characterized in the present study. CsCaM3 transcripts differed among the organs and tissues of cucumber plants and could be induced by HTs or abscisic acid, but not by sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…Moreover, zinc protein has a positive regulatory effect on HS [ 27 ]. According the report, overexpression of the calmodulin gene, namely CsCaM3 , prevents peroxidation and photosynthesis system damage in response to heat stress [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, zinc protein has a positive regulatory effect on HS [ 27 ]. According the report, overexpression of the calmodulin gene, namely CsCaM3 , prevents peroxidation and photosynthesis system damage in response to heat stress [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our data, a homologous VaCML44 gene shared 66% protein similarity to ShCML44 and was up-regulated under cold and salinity stress treatments (Figure 2). Overexpression of the CsCaM3 gene, which shared 100% protein similarity with VaCaM8 and VaCaM10, improved heat stress tolerance in cucumber [19]. Heat stress significantly increased transcript levels of the VaCaM8 and VaCaM10 genes after 6 h of treatment in our experiments (Figure 1).…”
Section: Discussionmentioning
confidence: 55%
“…Recently, a number of studies demonstrated that overexpression of plant CaM and CML genes can improve plant resistance to abiotic stresses [17][18][19][20]. For example, overexpression of the ShCML44 gene isolated from cold tolerant wild tomato enhanced the tolerance of a stress-sensitive tomato to cold, drought, and salinity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Csa3G824920 and Csa3G824940 that encode NBS-containing resistance-like proteins, and Csa3G825010 that encodes Calmodulin-like protein 1, were also found within this region. A previous study suggested that overexpressing CsCaM3 , a Calmodulin gene, could prevent peroxidation and photosynthesis system damage, and thus improve heat tolerance [ 16 ]. Two transcription factors including Csa3G824990 and Csa3G822440 that encodes an NAC domain protein and an AP2-like ethylene-responsive transcription factor were also found in the major QTL.…”
Section: Discussionmentioning
confidence: 99%
“…The expression patterns of Hsfs in cucumber were studied and most of them were up-regulated under heat stress, indicating those involved in heat stress tolerance [ 14 ]. There are also studies showed that auxin synthesis genes CsYUC8 and CsYUC9 were significantly up-regulated in heat-tolerance materials [ 15 ], and overexpressing CsCaM3 , a Calmodulin gene, could prevent peroxidation and photosynthesis system damage, and thus improve heat tolerance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%